Človeška in ptičja gripa: zakaj ptičja gripa ogroža človeštvo? - Perme, Janja (Obzornik zdravstvene nege, 2004)
Influenza is a frequent cause of respiratory illness resulting in significant mortality and morbidity, particularly in the elderly and those with underlyingchronic medical conditions. Despite influenza is not an eradicable disease and epidemics occur seasonally every winter, vaccination can effectively protect against infection. Vaccination is recommended also for healthcare workers to prevent transmission to their patients. Recently, antiviral agents from the group of neuraminidase inltibitors become available,which can be used for prevention and treatment of injluenza. Despitethis advances, the occurrence of recent widespread avian influenza outbreak among poultry in Asia reminds us of our vulnerability to an emerging pandemic which may case millions of victims. This epidemic was successfully limited and no significant human-to -human transmission of the avian influenzavirus occurred. Only individuals were infected who had close contact with infected poultry. In future, early recognition of epidemics of avian influenza and culling of all infected and diseased poultry is of critical importance. In addition, emergency plans, vaccines and stockpiling of antiviral medicaments are needed. The article summarizes the characteristics of human and avian influenza, modes of transmission, and prevention against this dangerous infection.
Keywords: Antagonists And Inhibitors; Antibodies, Viral; Antigeni virusni; Antigens, Viral; dihala; Disease Outbreaks; Epidemije; gripa; Influenca; Influenca A, virus človeški; Influenca A, virus ptičji; Influenca, cepivo; Influenza; Influenza A Virus, Avian; Influenza A Virus, Human; Influenza Vaccine; Neuraminidase; Nevraminidaza; Protitelesa virusna; ptičja gripa; Transmission; virusne bolezni; zaščita